2017
DOI: 10.1189/jlb.2ru1116-474r
|View full text |Cite
|
Sign up to set email alerts
|

cAMP: a multifaceted modulator of immune synapse assembly and T cell activation

Abstract: T Lymphocyte activation involves a substantial reorganization of the membranous and intracellular compartments. Signaling complexes assemble and dismantle in a highly ordered fashion in both compartments and orchestrate the activation of T cells with high sensitivity and specificity. TCR ligation leads to a short burst of cAMP production, which is centrally required for T cell activation; however, sustained elevations in intracellular cAMP concentrations are immunosuppressive. Emerging evidence of the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 225 publications
(242 reference statements)
2
66
0
Order By: Relevance
“…In addition to these, the A2AR also has the capacity to couple to the Golf that has expression limited to the brain, while the A2BR [52] and the A3R can also bind to the Gq/11 proteins that promote phospholipase C (PLC) dependent intracellular Ca 2+ signaling [40,53,54]. Stimulation of adenylate cyclase (AC) by Gαs proteins induced by stimulation of A2AR/A2BR in T cells results in the localized accumulation of cyclic AMP (cAMP) in microdomains that occur at the immunological synapse (IS) (reviewed in [55]). cAMP can bind to the regulatory domains on type 1 Protein Kinase A (PKA) targeted to lipid rafts in the IS by Ezrin, an A-kinase binding protein (AKAP) [55].…”
Section: The Diversity Of Adenosine Receptor Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these, the A2AR also has the capacity to couple to the Golf that has expression limited to the brain, while the A2BR [52] and the A3R can also bind to the Gq/11 proteins that promote phospholipase C (PLC) dependent intracellular Ca 2+ signaling [40,53,54]. Stimulation of adenylate cyclase (AC) by Gαs proteins induced by stimulation of A2AR/A2BR in T cells results in the localized accumulation of cyclic AMP (cAMP) in microdomains that occur at the immunological synapse (IS) (reviewed in [55]). cAMP can bind to the regulatory domains on type 1 Protein Kinase A (PKA) targeted to lipid rafts in the IS by Ezrin, an A-kinase binding protein (AKAP) [55].…”
Section: The Diversity Of Adenosine Receptor Signalingmentioning
confidence: 99%
“…Stimulation of adenylate cyclase (AC) by Gαs proteins induced by stimulation of A2AR/A2BR in T cells results in the localized accumulation of cyclic AMP (cAMP) in microdomains that occur at the immunological synapse (IS) (reviewed in [55]). cAMP can bind to the regulatory domains on type 1 Protein Kinase A (PKA) targeted to lipid rafts in the IS by Ezrin, an A-kinase binding protein (AKAP) [55]. This results in the phosphorylation of Src kinase, a negative regulator of Lck kinase, a key mediator of T-cell receptor (TCR) signaling activity (reviewed in [56]) [57][58][59].…”
Section: The Diversity Of Adenosine Receptor Signalingmentioning
confidence: 99%
“…Indeed, deletion and/or inhibition of components of the cAMP-PKA pathway modulate levels of other proteins that play a role in this pathway (Dupré et al, 2009;Erdogan and Houslay, 1997;Krumins and Gilman, 2006). In particular, we found that Coro1a À/À T cells expressed reduced amounts of the cAMP degrading enzyme PDE4, a central regulator of cAMP in T cells (Arumugham and Baldari, 2017). Furthermore, a PDE4 inhibitor, rolipram, phenocopied the coronin 1 depletion in an allograft rejection model.…”
Section: Discussionmentioning
confidence: 76%
“…High concentrations of cyclic AMP (cAMP) are known to suppress the activation and function of immune cells ( 1 ). Several bacterial pathogens exploit this property to evade the immune response by producing cAMP-elevating toxins, as exemplified by the ADP-ribosylating toxins of Vibrio cholerae or Bordetella pertussis (PT), which promote the accumulation of cAMP by activating cellular Gs proteins or inactivating cellular Gi proteins, respectively ( 2 , 3 ), or the adenylate cyclase (AC) toxins produced by Bordetella pertussis (CyaA), Bacillus anthracis [edema toxin (ET)], or Pseudomonas aeruginosa (ExoY), which directly catalyze cAMP production in infected cells ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%